Design of Table Chair Flexibility Products Using Antopometry Methods to Minimize Land Use - Yanatra Budi Pramana; Indra Dwi Febryanto (Tibuana, 2021)
In an increasingly advanced era, allproperty or home furniture is required to have arenewable innovation and efficiency. This is becauseproperty or home furniture currently has a very largemass or size. Large furniture sizes such as chairs andtables have an average area of 500cm2. Almost 90% ofIndonesian people have tables and chairs as the contentsof their household furniture. Not only functioned athome, in restaurants, cafes, malls, offices, in parks andall places where if there is interaction between humans,there must be chairs and tables as places for interaction.But sometimes the owners of chairs and tables oftencomplain about the size of the tables and chairs, so they need a large enough area to place these two items. Theproblem that exists in society today is the narrowing ofempty land in one place. Sometimes there is homefurniture that is not ergonomic, such as a chair that istoo high, a table that is too low and so on. By using thisanthopometric method, the measurements obtainedinclude a chair along the 95th percentile 25 cm, chairlength 33 cm 95th percentile, table length 68 cm 5thpercentile, chair height 39 cm 5th percentile, table height69 cm 5th percentile, and finally lower surface height. atable of 54 cm on the 95th percentile, and it is hoped thatthe manufacture of a chair flexibility table productdesign can overcome all the problems of land limitationsthat exist in today's society.